Benefits of long coherent integration for CZT‐based GPS signal acquisition. Issue 16 (1st August 2018) - Xu, Bing; Dou, Jie; Dou, Lei
Abstract : Due to its flexibility in calculating frequency spectrum, the chirp z‐transform (CZT) has been used in various applications where high‐frequency resolution is desirable, e.g. the acquisition of global positioning system (GPS) signals. However, the CZT is very time consuming when dealing with the very large size of input data. Thus, typically, only 1 ms data is used for GPS signal acquisition. In this Letter, the authors improve the acquisition precision and sensitivity of the CZT‐based acquisition by extending coherent integration time. To reduce computation load, they introduce a down‐sampling operation to the extended data without degrading acquisition performance. Results show that the CZT‐based acquisition with a coherent integration time of 10 ms obtains a frequency error of 5.9 Hz for the carrier‐to‐noise ratio (CNR) of 25 dB‐Hz and can acquire signals with a CNR down to 22 dB‐Hz.